CARDIOMETABOLIC RISK FACTORS OF PREGNANT PEOPLE REFERRED TO A CARDIO-OBSTETRIC PROGRAM IN A SAFETY NET HOSPITAL - Koura Sall, DO (Elsevier, 2024)
Therapeutic Area: ASCD/CVD in Women Background: Cardio-Obstetrics Programs are multidisciplinary groups that allow collaboration among cardiology and maternal-fetal medicine to decrease morbidity and mortality in pregnant people with cardiovascular disease. We aim to describe the characteristics of the patients referred to this program and evaluate the impact of CV risk factors on their outcomes. Methods: Retrospective chart review of patients seen in a Cardio-Obstetrics Program from November 2019-January 2024. Demographics, comorbidities, and maternal and fetal outcomes were recorded. This is an integrated multidisciplinary group of maternal fetal medicine, genetics, anesthesia, general cardiology, advanced heart failure and pulmonary hypertension specialists. Results: During the study period, 114 pregnant patients were referred to the Cardio-Obstetrics Program with CVD. The mean age was 31±7 years old, and body mass index was 33 ± 9.8 kg/m2. Regarding race/ethnicity, 41 (36%) identified as Latinx, 4 (3.5%) Asian, 47 (41.2%) Black, and 21 (18.4%) White. 58 (50.9%) were insured with Medicaid, 18 (15.8%) had private insurance and 33(28.9%) had no insurance. The CV risk factors were obesity in 57 (50%), tobacco use in 29 (37%), 16 (14%) with type 2 diabetes, 4(3.5%) with history of gestational diabetes, 32 (28%) had chronic hypertension, and 6 (5.3%) had dyslipidemia. Regarding their prior cardiac history at the time of pregnancy 4 (3.5%) had coronary artery disease, 3 (2.5%) with prior PCI, 10 (8.8%) with HFrEF, 2(1.8%) with HFpEF, 12 (10.5%) with peripartum cardiomyopathy, 12 (10.5%) with congenital heart disease, 5(4.4%) with moderate/severe mitral valve disease, 3(2.6%) with moderate/severe aortic valve disease, 13 (11.4%) with pulmonary hypertension and 11(9.6%) with supraventricular tachycardia. During pregnancy 24 (21.1%) had chronic hypertensive disorder, 34(29.8%) pre-eclampsia, 2 (1.8%) eclampsia, and 15 (13.2%) had gestational diabetes. Vaginal delivery occurred in 67 (58%) of the cases and termination in 4 (3.5%). The main complications observed were 1 (0.8%) cardiac arrest, 40 (35%) experienced pre-term labor and 4(3.5%) stillborn. There were no maternal deaths during the study period. Conclusions: In a population of primarily Medicaid-insured pregnant people managed by a cardio-obstetrics team, maternal outcomes are encouraging with no evidence of maternal death. Their comorbidities affect fetal outcomes. The cohort had several modifiable CV risk factors that can likely be addressed to decrease maternal morbidity.